2013
DOI: 10.1152/ajpheart.00446.2012
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase inhibits vascular smooth muscle cell proliferation and migration and vascular remodeling following injury

Abstract: Vascular smooth muscle cell (VSMC) activation promotes a synthetic phenotype that underlies many vessel growth disorders. In this regard it has been suggested that the metabolic sensor adenosine 5'-monophosphate-activated protein kinase (AMPK) has significant antigrowth and antimetastatic properties and may serve as a viable therapeutic target. In the current study we hypothesized that AMPK reduces neointima formation following balloon injury and that this occurs through reduction in VSMC proliferation and mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
87
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 62 publications
13
87
1
Order By: Relevance
“…Other studies indicated that the pleiotropic effects of metformin are mediated via activation of AMPK 61, 62. And it is also found that activating AMPK significantly suppress MMP‐9 activity to promote cell/extracellular matrix stability 63, 64. In the current study, we detected AMPK signalling pathway in neutrophils in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies indicated that the pleiotropic effects of metformin are mediated via activation of AMPK 61, 62. And it is also found that activating AMPK significantly suppress MMP‐9 activity to promote cell/extracellular matrix stability 63, 64. In the current study, we detected AMPK signalling pathway in neutrophils in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Primary VSMCs were obtained from thoracic aorta of male Sprague Dawley rats (ϳ125 g; Charles River Labs) by collagenase and elastase digestion and characterized morphologically as described (5). VSMCs were cultured in Dulbecco's modified Eagles medium (DMEM) supplemented with fetal bovine serum (FBS, 0.5-10%), 2 mM L-glutamine, and 1:500 dilution of 50 g/ml Primocin at 37°C in 95% air-5% CO 2, and were serially split and used through passage 10 (commercial) or passage 6 (primary) to avoid onset of phenotypic switching (1,11,23,24) unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of AMPK requires AMP binding and catalytic phosphorylation (17,20) and leads to energy-producing pathways being upregulated while energy-consuming pathways are shut off or rendered minimally active (7,8,17,(22)(23)(24). AMPK has many tissue-dependent functional targets leading to phosphorylation of key metabolic enzymes and, specifically in the vasculature, has been implicated in increased endothelial nitric oxide synthase activity and nitric oxide bioavailability, the promotion of angiogenesis, and cytostasis of commercial and primary VSMCs via inhibition of cell cycle progression (10,13,(22)(23)(24). Moreover, AMPK activation has been shown to inhibit neointima formation in rat arteries following injury (13,23).…”
Section: With the Use Of Commercial And Primary Preparations Along Wimentioning
confidence: 99%
See 2 more Smart Citations